A new multifunctional two-dimensional cobalt(II) metal–organic framework for electrochemical detection of hydrogen peroxide, luminescent sensing of metal ions, and photocatalysis. (15th January 2019) - Xiao, Qing-Qing; Liu, Dong; Wei, Ying-Li; Cui, Guang-Hua
Graphical abstract: A multifunctional 2D Co(II) metal–organic frameworks (NCST-1 ) with asql topology was synthesized under hydrothermal condition.NCST-1 /GCE exhibits remarkable performance for H2 O2 reduction. Furthermore, NCST-1 can act as a luminescent sensor for Fe 3+, Hg 2+, and Ag + in aqueous solution and serve as photocatalyst for the degradation of MB. Abstract: A new multifunctional cobalt(II)-based metal–organic framework, [Co(DCTP)(L)(H2 O)2 ] n (NCST -1, NCST = North China University of Science and Technology), was synthesized by self-assembly of Co(OAc)2 ·4H2 O with 1, 4-bis(benzimidazol-1-ylmethyl)-benzene (L) and 2, 5-dichloroterephthalic acid (H2 DCTP). Single-crystal X-ray diffraction analyses reveal thatNCST -1 is a 2D (4, 4) sheet, which is further expanded into a 3D supramolecular network by OH⋯O hydrogen bond interactions. A non-enzyme electro-catalytic sensor was developed for sensing hydrogen peroxide (H2 O2 ) based on theNCST -1, which was cast-coated on glassy carbon electrode (GCE). The modified sensor exhibited a remarkable performance for H2 O2 reduction with an extended liner range (5 μM–7 mM, 7 mM–18 mM), a fast response time (3 s), a high sensitivity (52.55 μA mM −1  cm −2 ), and a low detection limit (6.86 μM) in alkaline solution. Furthermore, NCST -1, as a luminescent probe, displayed prominent multifunctional sensing property for Fe 3+, Hg 2+ as well Ag + through fluorescence quenching effect. The emission intensity ofNCST -1 increases linearly with the increasing concentration of Fe 3+ with a Stern–Volmer constant ( K sv ) of 1.12 × 10 4  M −1 and a detection limit (LOD) of 0.13 μM in aqueous solution. For mercury ion (II), K sv  = 7.58 × 10 3  M −1 and LOD = 1.10 μM. For silver ion (I), K sv  = 6.22 × 10 3  M −1 and LOD = 1.33 μM. Finally, the photocatalytic activities ofNCST -1 were evaluated in the degradation of methylene blue (MB), Rhodamine B (RhB), and methyl orange (MO). The degradation efficiency for MB reached up to 91.3%, althoughNCST -1 hardly showed degradation ability towards RhB and MO.